Relación entre la Gestión de Inventarios y Disponibilidad de Medicamentos en el Hospital Público Dr. Francisco Vásquez Balda de Pedernales en Manabí - Acuña García, José Hipólito (My University, 2025)
Inefficient management of pharmaceutical inventories in public hospitals can lead to shortages, financial losses, and interruptions in essential medical treatments for vulnerable populations. This research aimed to analyze the relationship between inventory management and its direct impact on medication availability at the Dr. Francisco Vásquez Balda Public Hospital, located in the Pedernales canton of Manabí province. A quantitative, descriptive, and non-experimental study was conducted through direct observation and the application of structured surveys to staff responsible for pharmaceutical inventory management, as well as to users. The results reveal multiple shortcomings in the current healthcare system, such as delays in medication replenishment times, poor communication between involved areas, a lack of adequate technology for automated stock control, and insufficient staff training. Given this situation, we propose implementing an optimization model that integrates specialized software with institutional strengthening through a continuous improvement plan. The research not only seeks to optimize inventory management and ensure the continued availability of medications at this hospital, but also provides a solid foundation for future interventions and the development of policies aimed at strengthening the health system and improving the quality of care for users.
Una gestión ineficiente de los inventarios farmacológicos en hospitales públicos puede derivar en desabastecimientos, pérdidas económicas e interrupción de tratamientos médicos esenciales en poblaciones vulnerables. Esta investigación tuvo como objetivo analizar la relación entre la gestión de inventarios y su impacto directo en la disponibilidad de medicamentos del Hospital Público Dr. Francisco Vásquez Balda, perteneciente al cantón Pedernales en la provincia de Manabí. Se realizó un estudio cuantitativo, descriptivo y no experimental mediante la observación directa y aplicación de encuestas estructuradas al personal encargado de la gestión de inventarios farmacéuticos, así como a los usuarios. Los resultados evidencian múltiples falencias en el sistema de salud actual, como demoras en los tiempos de reposición de medicamentos, comunicación deficiente entre áreas involucradas, inexistencia de tecnología adecuada para el control automatizado del stock y escasa capacitación del personal. Ante esta situación se propone implementar un modelo de optimización que integre software especializado junto con el fortalecimiento institucional mediante un plan de mejora continua. La investigación no solo busca optimizar la gestión de inventarios y asegurar la disponibilidad continua de medicamentos en este hospital, sino que además proporciona una base sólida para futuras intervenciones y el desarrollo de políticas orientadas a fortalecer el sistema de salud para mejorar la calidad de atención a los usuarios.
Keywords: GESTIÓN; INVENTARIO; MEDICAMENTOS